14-day pantoprazole- and amoxicillin-containing high-dose dual therapy for Helicobacter pylori eradication in elderly patients: A prospective, randomized controlled trial - Yang, Qinyu; He, Cong; Hu, Yi; Hong, Junbo; Zhu, Zhenhua; Xie, Yong; Shu, Xu; Lu, Nonghua; Zhu, Yin (Frontiers in Pharmacology, 2023)
Background: Currently, the management of Helicobacter pylori (H. pylori) infection in elderly patients is controversial. We investigated whether high-dose dual therapy would serve as the first-line therapy in elderly patients. Methods: This was a single-center, randomized study of 150 elderly patients with H. pylori infection who were randomly assigned to 14-day therapy with pantoprazole 40 mg 3 times daily and either amoxicillin 1000 mg 3 times daily or amoxicillin 1000 mg twice daily, clarithromycin 500 mg twice daily and bismuth 220 mg twice daily. H. pylori eradication was evaluated by a 13C-urea breath test 4 weeks after the completion of treatment. Results: Successful eradication was achieved in 89.3% of the high-dose dual therapy (HDDT) group in the intention‐to‐treat (ITT) analysis, 91.7% in the modified intention-to-treat (mITT) analysis, and 93.0% for per‐protocol (PP) analysis which was similar to the bismuth-containing quadruple therapy (BQT) group (86.6%, 87.8%, and 90.2%, respectively). There were no significant difference between the HDDT group and the BQT group in the ITT analysis (P=0.484), mITT analysis (P=0.458), or PP analysis (P=0.403). HDDT was associated with fewer side effects (10.6% of patients) than BQT (26.6%) (P=0.026). Conclusion: In this trial, we found that 14-day HDDT had a similar eradication rate to BQT but fewer side effects, which may be better for elderly patients.